Exploring the relationship between dietary index for gut microbiota and cognitive function - Sun, Changhu; Tan, Tingting; Chen, Zeping (Frontiers in Nutrition, 2025)
BackgroundSignificant correlations exist between gut microbiota, dietary habits, and cognitive function; the objective of this research was to evaluate the correlation between the dietary index for gut microbiota (DI-GM) and cognitive performance. The primary objective of this study was to evaluate the strength and direction of the association between Dietary Index for Gut Microbiota (DI-GM) scores and cognitive performance among older adults, and to further explore whether a dose-response relationship exists, thereby informing potential dietary strategies for cognitive risk stratification.MethodsComplete DI-GM and cognitive function evaluation data for older adults were taken from the 2011–2014 National Health and Nutrition Examination Survey (NHANES) database. Cognitive function was assessed by standardized test scales. The weighted linear regression models were used to examine the association between DI-GM and cognitive function. Restricted cubic spline and threshold analysis evaluated the existence of non-linear correlations among variables. Subgroup studies were conducted to evaluate the consistency of the connection across different demographics.ResultsThe outcome analysis showed that among the 2,207 participants, there was a positive and statistically significant relationship between higher DI-GM scores and scores of beneficial gut microbiota and total scores of cognitive functions (β = 0.03, 95% CI: 0.01–0.05, P = 0.034). Both RCS and threshold analyses confirmed the linear correlation between DI-GM and beneficial gut flora and total scores of cognitive functions (P for non-linear > 0.05). Additionally, our study demonstrated that the correlation between DI-GM and total scores of cognitive functions was maintained in subgroup analyses (P for interaction > 0.05).ConclusionThe findings of the study indicated that DI-GM profoundly impacts cognitive performance, which suggests that dietary modifications based on DI-GM may help lower the level of cognitive impairment in the elderly, but further high-caliber research is required to elucidate the precise processes and application modalities, and to provide more effective strategies for improving cognitive function in the elderly.